Students Reasons and Attitudes for Code-Switching in Language classroom Case of Kazakhstan (Bilingual situation) - L.N, Orynbek Gulnar; Gulzhan, Akmetbek; L.N, Erik Gulnur; Gaziza, Koshirbayeva; Gauhar, Baltabayeva (International Journal of Psychosocial Rehabilitation, 2020)
In bilingual and multilingual communities, it is often the case that people often code switch from one language to another in their daily conversation. For that reason, One of the vital decisions of teachers, educator and even curriculum designers is the arbitrary choice of language in classroom. These sorts of decisions have salient effect in learners’ success in language proficiency. Both teachers and learners have responsibility to this kind of selection. Utilization of Code Switching is worldwide strategy. There are extensive studies about Code Switching and Code Mixing. Code Switching is a kind of contextual sign which range from phonological, lexical and syntactic selections to various sorts of Code Switching and style shifting. Therefore, the researcher tried to introduce Code Switching as well as Code Mixing previous researches. Furthermore, the author has discussed about various approaches and attitudes towards Code switching, and Code Mixing. Then, the main differences between Code switching and Code mixing are explained briefly.